Impact of aldosterone on osteoinductive signaling and vascular calcification - Lang, Florian; Ritz, Eberhard; Alesutan, Ioana; Voelkl, Jakob (Nephron. Physiology, 2014)
Vascular calcification is frequently found already in early stages of chronic kidney disease (CKD) patients and is associated with high cardiovascular risk. The process of vascular calcification is not considered a passive phenomenon but involves, at least in part, phenotypical transformation of vascular smooth muscle cells (VSMCs). Following exposure to excessive extracellular phosphate concentrations, VSMCs undergo a reprogramming into osteo-/chondroblast-like cells. Such ‘vascular osteoinduction' is characterized by expression of osteogenic transcription factors and triggered by increased phosphate concentrations. A key role in this process is assigned to cellular phosphate transporters, most notably the type III sodium-dependent phosphate transporter Pit1. Pit1 expression is stimulated by mineralocorticoid receptor activation. Therefore, aldosterone participates in the phenotypical transformation of VSMCs. In preclinical models, aldosterone antagonism reduces vascular osteoinduction. Patients with CKD suffer from hyperphosphatemia predisposing to vascular osteogenic transformation, potentially further fostered by concomitant hyperaldosteronism. Clearly, additional research is required to define the role of aldosterone in the regulation of osteogenic signaling and the consecutive vascular calcification in CKD, but more generally also other diseases associated with excessive vascular calcification and even in individuals without overt disease.
Gesehen am 23.10.2020